Grundtvigs dannelsesbegreb mellem national dannelse og erhvervsorienteret uddannelse - Lyby, Thorkild C. (Grundtvig-studier, 2004)
Grundtvigs dannelses begreb mellem national dannelse og erhvervsorienteret uddannelse[Grundtvig ’s Concept o f a “folkelig ’’ Education between nationalist Education and professional Training]By Thorkild Lyby Grundtvig’s concept of a folkelig education has elements of both a truly nationalist education and a professional training aimed at occupational competence, but is not completely covered by either of these. Against the background of his contemporary social structure, he was sceptical towards an institutionalised primary school, especially if it was meant to function as preparation for an occupational training. He despised the grammar-school which in his view served only to distance the future professionals from the people they were supposed to serve. As an alternative, he expounded a plan for a large state-run highschool in Soro where there could be developed a folkelig education which would be common to both ordinary folk and the elite, English Summaries / danske resuméer while strictly professional training could take place as a supplement at ‘nurseries’ or professional seminaries.The distinctive nationalist dimension of his concept of folkelig education is connected partly with the general trends of the age and partly with Denmark’s particular position in his day. However, the heart of the matter was indubitably the idea of a human communality cutting across the differences, a communality which had nationality as a natural, but open framework.The folk-highschool movement which went on historically to develop itself, thus diverges markedly from Grundtvig’s original thinking on the highschool. Yet it must be said that the idea of human development and sense of communality cutting across the differences has been a key element in its work and that this has been one of the most important things it has contributed to Danish cultural life.Today it is in difficulties, insofar as it is under pressure partly from a dramatic fall in the number of young people of highschool age and partly from the influence of the management culture upon educational policy with its demand for a quantifiable end-product of all teaching. It has been proposed that the survival of the folk-highschool be secured by introducing examinations. This however would deal a blow to that freedom of teaching which has itself been a basis of its special character and its work, and which still today remains the basis of its ability to make its special contribution to a folkelig education. In an age of globalisation and internationalisation this is a greater imperative than ever.